Evaluation of antimicrobial and antioxidant potential of Oxalis corymbosa extracts - Attique, Sana; Ibrahim, Muhammad; Khan, Changeez; Ali, Akbar; Qadir, Rahman; Khan, Ajmir; Al-Salahi, Rashad; Abuelizz, Hatem A.; da Silva Medeiros, Paulo; Moreira Sampaio, Olívia; Campos Curcino Vieira, Lucas (John Wiley and Sons, 2024)
This work aimed to assess the antioxidant and antimicrobial properties of Oxalis corymbosa extracts. Biochemical analyses were conducted on various plant parts, utilizing enzymatic and non-enzymatic assays. Parameters such as total soluble protein, chlorophyll, and carotenoid contents were also evaluated to elucidate the role of bioactive chemical compounds. The antimicrobial screening of extracts was performed against the bacterial and fungal strains Escherichia coli, Staphylococcus aureus, and Candida albicans, respectively. Results indicated that chlorophyll a, chlorophyll b, total chlorophyll, carotenoid content, anthocyanin content, catalase, peroxidase, and superoxide dismutase were most abundant in the O. corymbosa leaves. Moreover, total ascorbate peroxidase content, total phenolic content, and total flavonoid content were found to be higher in the roots compared to other parts. High-performance liquid chromatography analysis identified chlorogenic acid as the major component, followed by gallic acid, caffeic acid, quercetin, and salicylic acid. Regarding antibacterial potential, each extract exhibited significant activity, with methanolic and ethyl acetate extracts demonstrating the maximum inhibition zone against S. aureus and E. coli, respectively. These findings highlight the substantial antioxidant and antibacterial potential of different parts of O. corymbosa, suggesting their promising applications as ingredients in various nutraceutical products.